CGRP Inhibits Apoptosis and Protects against Extraocular Muscle Atrophy in Patients with Concomitant Exotropia through the AKT/CREB Pathway - Xiaoping Hong; Fadian Ding; Xingting Chen; Feng Gao; Qicai Liu (Journal of Bio-X Research)
Concomitant exotropia is a common chronic eye disease characterized by abnormal movement of the extraocular muscles caused by a functional imbalance of the nerves related to the movement of the extraocular muscles. This study revealed that the expression levels of S-100β and the muscle area decreased in the extraocular muscles of patients with concomitant exotropia, whereas the expression of calcitonin gene-related peptide (CGRP) increased. In CGRP-KO rats, low expression of CGRP was positively correlated with muscle atrophy. Moreover, the expression level of muscle cells, which are fast myosin heavy chain positive and slow myosin positive in CGRP-KO rats, was lower than that in the control group. Drug intervention experiments further confirmed the inhibitory effect of CGRP on muscle atrophy. The level of apoptosis in the extraocular muscles of CGRP-KO rats was significantly greater than that in the control group (P < 0.05), and the phosphorylation level of AKT/CREB in the extraocular muscles of patients with concomitant exotropia was greater than that in the control group. The increased expression of CGRP in the extraocular muscles of patients with concomitant exotropia may inhibit the apoptosis of extraocular muscle cells through the AKT/CREB signaling pathway and participate in the protective effect of the extraocular muscles in concomitant exotropia.